Preditores abióticos e bióticos da abundância de uma macrófita nativa e uma macrófita invasora em um reservatório subtropical. - Florêncio, Fernanda Moreira (2021)
The invasion success of non-native species depends on several factors, and native populations and biotic characteristics of non-native environments can offer resistance to non-native species development. Reservoirs can facilitate submerged macrophyte invasion once it modifies the environment and provides favorable abiotic conditions to macrophyte establishment and development. However, previous colonization of native species can resist the development of invasive ones through priority effects. In this investigation we used large data-set (1120 samplings during 4 years) obtained in the Itaipu Reservoir (Brazil/Paraguay) to assess the relationship between the abundance of the native submerged macrophyte Egeria najas and of the invasive Hydrilla verticillata and the water level, littoral slope and Secchi disk depth. We also investigated how the concomitant and previous abundance of both macrophytes correlates. A spatial-temporal modeling was applied using Integrated Nested Laplace Approximations method, which controls the effect of spatial-temporal autocorrelation. Our results indicate an important role of water transparency, littoral slope and water level oscillations (in terms of amplitude and increased hydrometric level), in a short period of time (30 days) for the temporal dynamics of the abundance of both species. However, alterations of the hydrometric levels and of the littoral slope affected H. verticillata to a greater extent than E. najas. In addition, the abundance of each species was related with its own abundance in previous samplings, highlighting the importance of vegetative propagule pressure and resistance structures for population recovery. The magnitude of the interaction between both species in concomitant occurrence in the same site was abundance dependent.